2002
DOI: 10.1007/s10350-004-6106-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Endorectal Ultrasonography in Preoperative Staging of Rectal Tumors

Abstract: The accuracy of endorectal ultrasonography in assessing the depth of tumor invasion, particularly for early cancers, is lower than previously reported. The technique is more precise in distinguishing between benign tumors and invasive cancers and between tumors localized to the rectal wall and tumors with transmural invasion. Differences in image interpretation may in part explain discrepancies in accuracy between studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
177
0
36

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(219 citation statements)
references
References 28 publications
6
177
0
36
Order By: Relevance
“…The accuracy of T-staging, in our study, was 64.3 % in TRUS. Garcia-Aguilar et al [9], in a study conducted at a single institute, reported the overall accuracy of TRUS for detecting rectal wall penetration as 69 %. But in their study, 76.4 % of patients had lesions with lower T-stages (T0 to T2).…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of T-staging, in our study, was 64.3 % in TRUS. Garcia-Aguilar et al [9], in a study conducted at a single institute, reported the overall accuracy of TRUS for detecting rectal wall penetration as 69 %. But in their study, 76.4 % of patients had lesions with lower T-stages (T0 to T2).…”
Section: Discussionmentioning
confidence: 99%
“…Ao analisar o envolvimento ganglionar, observou-se uma sensibilidade de 39%, o que difere de alguns estudos publicados que apontam para valores mais altos de sensibilidade, mas que vai ao encontro de outro estudo, que demonstra uma sensibilidade de 33% na avaliação do N 23,25,26,40 . Isso poderá ser explicado pelo enviesamento de publicação referido anteriormente, mas também pelo facto da inclusão nesses estudos de doentes submetidos à terapia neoadjuvante, que poderá resultar numa subestimação da sensibilidade da ecografia endorectal 39,40 .…”
Section: Discussionunclassified
“…Esses valores obtidos estão de acordo com estudos anteriores que apontam para valores semelhantes de valor preditivo positivo e negativo 39 . Quanto à eficácia, esta foi de 89% para T1, de 75% para T2 e T3 e de 97% para T4, conforme resultados demonstrados por estudos anteriores que apontam para níveis de eficácia muito altos da ecografia endorectal na avaliação da invasão tumoral na parede do recto 17,23,26,39 .Ao analisar o envolvimento ganglionar, observou-se uma sensibilidade de 39%, o que difere de alguns estudos publicados que apontam para valores mais altos de sensibilidade, mas que vai ao encontro de outro estudo, que demonstra uma sensibilidade de 33% na avaliação do N 23,25,26,40 . Isso poderá ser explicado pelo enviesamento de publicação referido anteriormente, mas também pelo facto da inclusão nesses estudos de doentes submetidos à terapia neoadjuvante, que poderá resultar numa subestimação da sensibilidade da ecografia endorectal 39,40 .…”
unclassified
See 1 more Smart Citation
“…Endorectal sonography is reported to be 69% accurate for tumor penetration of the rectal wall, and 64% accurate for nodal metastasis (42). However, it is highly operator-dependent, has limited depth penetration, and cannot be performed in stenotic tumors or tumors in the upper rectum (41)(42).…”
Section: Discussionmentioning
confidence: 99%